Concentration and source identification of polycyclic aromatic hydrocarbons (PAHs) in PM10 of urban, industrial and semi-urban areas in Malaysia - Mazrura, Sahani; Mohd Talib, Latif; Kok, Meng Chan (2014)
Particulate matter (PM10) associated with polycyclic aromatic hydrocarbons (PAHs) in ambient air were determined at two sites within the Klang Valley, Kuala Lumpur(urban, KL) and Petaling Jaya (industrial, PJ),and one site outside the Klang Valley, Bangi (semi-urban, BG). This study aimed to determine the concentration and distribution of PAHs in PM10and the source of origin through principal component analysis(PCA)and diagnostic ratio analysis. This study also assessed the health risk from exposure to airborne BaPeq.PM10samples were collected on glass ﬁber ﬁlter paper using a High Volume Sampler (HVS) for 24 h betweenSeptember2010 and April2011. The ﬁlter papers with PM10were extracted using dichloromethane-methanol(3:1), and analysis of 16 USEPA priority PAHs was determined using gas chromatography with mass spectra(GCeMS). Health risk assessment was estimated using toxic equivalency factors (TEFs) and incremental lifetime cancer risk (ILCR) which quantitatively estimate the exposure risk for age speciﬁc group. The results showed that the total PAHs concentrations throughout seasonal monsoons for KL, PJ and BG ranged from 1.33 ng m3 to 2.97ng m3, 2.24 ng m3to 4.84 ng m3 and 1.64ng m3 to 3.45 ng m3 respectively. More than 80% of total PAHs consisted of 5-ring and 6-ring PAHs such as benzo[a]pyrene (BaP), indeno[1,2,3-cd]pyrene(IcP), benzo[b]ﬂuoranthene (BbF), benzo[k]ﬂuoranthene (BkF) and benzo[g,h,i]perylene (BgP). The presence of benzo[g,h,i]perylene (BgP) with high concentration at all locations suggested a source indicator for trafﬁce mission. PCA and diagnostic ratio analysis also suggested substantial contributions from trafﬁc emission with minimal inﬂuence from coal combustion and natural gas emissions. The use of total Ba P eq concentration provide a better estimation of carcinogenicity activities, where they contributed to more than 50% of the potential health risk. Health risk assessment showed that the estimated incremental lifetime cancer risk(ILCR) from exposure to airborne BaP eq is negligible at all sampling sites for all age speciﬁc group.